The Role of Internal Control in Moderating the Effect of Compensation Appropriateness and Accounting Information Systems on Accounting Fraud - Lufriansyah, Lufriansyah; Siregar, Qahfi Romula (AIBPM Publisher, 2025)
This study aims to examine and analyze the influence of compensation suitability and accounting information systems on accounting fraud, with internal control serving as a moderating variable in hospitals in Medan City. This research employed a quantitative approach, and primary data were collected through questionnaires. The sampling technique used was quota sampling, involving 36 respondents. Data analysis was conducted using Partial Least Squares. The results indicate that compensation suitability has a positive and significant effect on accounting fraud in hospitals throughout Medan City. Accounting information systems also have a positive and significant effect on accounting fraud. Furthermore, internal control has a positive and significant moderating effect on the relationship between compensation suitability and accounting fraud, as well as on the relationship between accounting information systems and accounting fraud in hospitals throughout Medan City.